Hafnia alvei causing late onset sepsis in neonates: report of two cases and review of literature - Basani, Laxman; Aepala, Roja (International Journal of Contemporary Pediatrics, 2018)
Hafnia alvei, a Gram negative motile bacillus that belongs to Enterobacteriaceae family is rarely associated with infection in pediatric patients and is exceptionally rare in the neonatal period. H. alvei is ubiquitous in the environment, causing infections in debilitated and immuno-compromised patients with few cases being reported in neonates. We report two cases of late onset sepsis in term neonates caused by H. alvei that were successfully treated in our unit. To the best of our knowledge, infection due to H. alvei has not been reported in neonates from India. Hafnia alvei causes infection rarely in neonates. Because it can cause nosocomial outbreaks, awareness regarding this uncommon pathogen and initiation of appropriate antibiotic therapy improves the outcome and prevents mortality.